Financial Literacy and Financial Self-Efficacy to Improve Financial Bootstrapping and business performance - Dhoni Rizky Widya Mardika; Nur Listiani; Farah Amalia (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
Analyzing the impact of financial self-efficacy and financial literacy on financial bootstrapping is the aim of this study. Additionally, this study looked at how financial bootstrapping affected the performance of businesses. The importance of financial bootstrapping as a tactic to be used in circumstances where capital is limited is clarified by this study for MSME. MSMEs are expected to need to increase their financial self-efficacy and financial literacy in order to improve financial bootstrapping. Purposive sampling methods were employed to collect data from MSME in Indonesia's Central Java Province. A total of 520 samples were tested using structural equation modeling. Financial bootstrapping is positively and statistically significantly impacted by financial self-efficacy and financial literacy. Business performance is significantly and favorably impacted by financial bootstrapping. Given the narrow focus of this study, it is conceivable that the limited economic circumstances of each micro, small, and medium-sized business (MSME) may make the use of financial bootstrapping difficult in other situations. To sustain positive business performance in the early phases of their venture, entrepreneurs may use financial bootstrapping strategies. The organization needs to improve financial self-efficacy and financial literacy in order to make financial bootstrapping easier to implement. The government might raise awareness of the importance of financial management and provide financial literacy training to encourage efficient financial management. Several studies have looked into how financial bootstrapping affects business performance and have found that it can have a favorable effect on a company's success. Nevertheless, no study has been done to look at the variables that could influence financial bootstrapping. The conclusion of this study is that the higher the financial literacy and self-efficacy, the more financial bootstrapping increases, besides that financial bootstrapping can improve business performance.